P531 Tuberculin skin test conversion rate in inflammatory bowel disease patients receiving anti-TNFα agents. (16th January 2018) - Fragaki, M; Paspatis, G; Karmiris, K
Abstract: Background: Anti-TNFα therapy increases the risk of tuberculosis (TB) (re)-activation in inflammatory bowel disease (IBD) patients. Purified protein derivative tuberculin skin test (PPD-TST) is considered a pre-requisite at baseline. However, few data exist regarding the kinetics of this test during therapy. Therefore, our study investigated the conversion rate of PPD-TST in IBD patients under anti-TNFα treatment. Methods: Anti-TNFα treated IBD patients followed up in our centre with a baseline PPD-TST underwent a sequential one during therapy. Those with a positive PPD-TST either at baseline or during therapy ( d > 10 mm in naïve and d > 5 mm in those exposed to immunomodulators [IMS]) received 300 mg isoniazid orally for 9 months. Results: Sixty-eight IBD patients have been enrolled so far (males: 51.47%, Crohn's disease: 82.35%). Median age at IBD diagnosis was 33.1 years [IQR: 20.3, range: 16.7–66.7]. Median duration of IBD was 7.7 months [IQR: 9.8, range: 1.4–32.7]. Nine patients (13.23%) had a positive PPD-TST at baseline. Fifty-eight patients have undergone a second PPD-TST (median time between the first and second PPD-TST: 27.10 months [IQR: 41.22, range: 6.3–190.1]). Nineteen patients were under combination therapy with an IMS at the second PPD-TST. In seven patients with a positive baseline PPD-TST, this remained positive (in five patients the diameter was decreased and in two increased) and in one it turned negative. Out of the remaining 50 patients with a negative baseline PPD-TST, 10 (20%) exhibited a positive second PPD TST; three of them were receiving infliximab for less than 3 years and seven of them adalimumab (three for less and four for more than 3 years). Only 3 of 10 were under combination therapy. No case of active tuberculosis has been detected in this cohort so far. All patients with a PPD-TST conversion received anti-tuberculous treatment. Conclusions: A positive PPD-TST followed by anti-TB treatment before the initiation of anti-TNFα in IBD patients was not associated with an increased rate of TB infection during therapy. In one-fifth of the patients with a negative baseline PPD-TST the test exhibited conversion but without any undesirable consequence if so treated.